Design and analysis of wide and multi-bands multi-input multi-output antenna for 5G communications - Karrar Shakir Muttair; Ali Zuhair Ghazi Zahid; Oras Ahmed Shareef; Raed Hameed Chyad Alfilh; Ahmed Mohammed Qasim Kamil; Mahmood Farhan Mosleh (Institute of Advanced Engineering and Science, 2022)
A good antenna design has played an essential role in the design of wireless communication systems, international companies are looking for the best design that suits their products in terms of size, bandwidth, gain, cost, and performance. In this paper, three antenna models are designed for fifth-generation (5G) communications, the first model is a single antenna, the second model is a two-ports multi-input multi-output (MIMO) antenna, and the third model is a four-ports MIMO antenna. The geometric dimensions of a single antenna are 20×37×1.6 mm3, the two-ports antenna dimensions are 44×37×1.6 mm3, while the four-ports antenna dimensions are 74×44×1.6 mm3. The design of these antennas was based on the latest strategies in terms of their small sizes and operating from 13.5 to 20 GHz in wide and multiple bands to be compatible with all advanced communication devices. Based on the results that emerged, it was noted that the reflection coefficient (S11) < -10 dB and has better isolation between the ports is < -26 dB. While the envelope correlation coefficient (ECC) value is < 1.036×10-9, and the diversity gain (DG) value is 10 dB. All antennas proposed operate in ultra-wideband (UWB) which is very necessary for 5G communications devices.